PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) JOMBANG - Septian Ragil Anandita; Lubis Kurniawan; Wisnu Mahendri (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
The purpose of this study was to determine the effect of compensation and activities on employee performance at the Jombang Public Works and Spatial Planning Service. The method used in this study is a quantitative method. The population in this study found 159 employees while the sample found 50 respondents using a representative formula. Data were collected using the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results showed that partially the compensation variable had a positive but not significant effect on employee performance, while the variable had a positive and significant effect on employee performance. Simultaneously, compensation and activity variables have a positive and significant impact on the performance of employees of KPP Pratama Jombang. The results of the analysis of the coefficient of determination obtained are 0.402 or 40.2%, which means that the contribution of the Motivation and Work Discipline variable to employee performance is 40.2% while the remaining 59.8% is influenced by other variables outside the regression equation or other variables not examined.